The Network Evolution of the Internationalizing Firm - Sérgio Fernando Loureiro Rezende; Alysson Moreira Alves; Dirley dos Reis Moreira Bicalho; Ângela França Versiani (BBR: Brazilian Business Review)
This paper analyses the network evolution of the internationalizing firm, focusing on a generative mechanism called preferential attachment. Preferential attachment means that more connected actors are likely to form more relationships. This paper uses longitudinal quantitative data of a single case of the internationalization of an American multinational firm’s operational division in the Brazilian market. The data analysis is based on Clauset et al.’s (2009) computational algorithm and PAFit, a new statistical method. The aim is to identify the extent to which the network evolution follows a power-law distribution and the degree to which preferential attachment affects the network evolution. It finds that the network evolution of the internationalizing firm follows a power-law distribution. It is affected by a sub-linear form of preferential attachment. Few actors accumulate a disproportionally high number of relationships. The preferential attachment does not homogeneously manifest itself in the network evolution. It has a strong effect on the network onset. This paper contributes by advancing a relational, process-based approach to the internationalization of the firm. It shows that the network evolution of the internationalizing firm grows over time and becomes sparser. More connected actors form hubs, meaning increased status, more power and resources.